2008
DOI: 10.1063/1.2967517
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature plasticity anomaly in the bulk metallic glass Zr64.13Cu15.75Ni10.12Al10

Abstract: The plastic deformation and compression fracture of cylindrical samples of the bulk metallic glass Zr64.13Cu15.75Ni10.12Al10 have been studied in the temperature range 300–4.2K. The deformation curve at 300K is serrated due to the propagation of narrow shear bands. Catastrophic, uncontrollable fracture of samples, occurring as a result of the propagation of a macroscopic shear band with speed (of the order of 103m∕s) comparable to the sound speed, is observed at deformation ∼3–4%. When the temperature is lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…(6). Tabachnikova et al [12] have shown that with the temperature decrease to 77 K from room temperature, both the compressive strength and plasticity of Zr 64. 13 225 at 77 K might also be ascribed to the decrease of the STZ volume due to low temperature, where nano-scaled "chevron" patterns rather than vein patterns on the low temperature fracture surface indicate an apparent decrease in the plasticity [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(6). Tabachnikova et al [12] have shown that with the temperature decrease to 77 K from room temperature, both the compressive strength and plasticity of Zr 64. 13 225 at 77 K might also be ascribed to the decrease of the STZ volume due to low temperature, where nano-scaled "chevron" patterns rather than vein patterns on the low temperature fracture surface indicate an apparent decrease in the plasticity [7].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore expected that these materials should not undergo DBT process. However, the DBT phenomena, as first reported by Wu and Spaepen [6], have been widely observed in metallic glasses [7][8][9][10][11][12][13][14][15][16]. Due to the practical and scientific significance of this behavior, it has attracted much attention.…”
Section: Introductionmentioning
confidence: 99%
“…Such plasticity improvement was attributed to multiple-nucleation of shear bands at low temperature [1,5,7]. Nevertheless, there are also some sporadic papers showing different trends [13][14][15]. Thus, one question naturally arises.…”
Section: Introductionmentioning
confidence: 99%
“…Low-temperature measurements have also been performed [109][110][111] and demonstrated the increase in the maximum compressive stress with decreasing testing temperature. The stress-strain diagrams for the typical glassy Zr 64.13 Ni 10.12 Cu 15.75 Al 10 alloy tested at room temperature and close to boiling liquid nitrogen (LN 2 ) temperature are shown in Figure 5.…”
Section: Deformation Of Bulk Metallic Glasses At Cryogenic Temperaturementioning
confidence: 99%